The Effect of Exercise on Urinary Gamma-Glutamyltransferase and Protein Levels in Elite Female Karate Athletes - Shavandi, Nader (Tehran University of Medical Sciences, 2012)
PURPOSE: Post exercise proteinuria and increased urinary Gamma-Glutamyl transferase (GGT) levels can be indicative of exercise-induced renal damage. The aim of this investigation is to study the effect of one session of intensive training on renal damage markers and compare their values to those 6 hours after training. METHODS: In this cross-sectional study with pre- and post-test design, 10 elite volunteer female athletes were selected and participated in one training session (2 hours). Urine samples were collected before training, one hour after training, and 6 hours after training. Urinary protein (Pr), creatinine (Cr), and GGT values were measured through laboratory methods and then Pr/Cr and GGT/Cr ratios were computed. RESULTS: There were significant differences between values of protein, GGT and Creatinine in the three sampling phases (P<0.05). However, no significant differences were observed between values for GGT/Cr and Pr/Cr ratio. There were significant differences between the mean values of Creatinine, protein and GGT within pre-exercise and 1 hour post-exercise and within 1 hour post-exercise and 6 hours post-exercise (P<0.05). CONCLUSION: It seems that a session of karate training does not result in renal damage and athletes can continue training after 6 hours.